Productivity of Major Pulses in Cropping Systems Adopted by Farmers in Chhattisgarh Plains in India - , Shivaji Limje; , M. A. Khan; , Sevak A. Dhenge (Archives of Current Research International, 2025)
The present study was conducted in four districts comprising 320 sample farmers in pulse-based cropping systems in Chhattisgarh plains to ascertain their knowledge, production and productivity pulse crops. The selected pulse growing farmers were interviewed with the help of a well-structured and pre-tested interview schedule. The findings of the study showed that, rice (40.1-48q/ha), wheat (12.1-14q/ha), gram (8-10q/ha), arhar (7.1-9q/ha), mung (6.1-8q/ha), urd, peas, and lathyrus (5.1-7q/ha), lentil (6q/ha) and soybean (5q/ha) are among the pulse crops with higher productivity at Chhattisgarh Plains. Moreover, the majority of the respondents, cultivated local variety of gram crop followed by mung, arhar, urd, lentil, pea and lathyrus crop. The results suggested a need for more efforts to make the farmers of the sample area aware of the adoption of the improved verities of the pulses, cereals, and oilseed crops by demonstration, training, field visits, and farm publications also arrange the market for selling of farm produced without any middleman that can help in getting more profit. The finding also suggested addressing the constraints about the production of the improved varieties of pulses, cereals, and oilseed crops.